Bacterial diseases of grapevine - Szegedi, E.; Civerolo, E. L. (International Journal of Horticultural Science, 2011)
Grapevines are affected by three major bacterial diseases worldwide, such as bacterial blight (Xylophilus ampelinus), Pierce’s disease (Xylella fastidiosa) and crown gall (Agrobacterium vitis). These bacteria grow in the vascular system of their host, thus they invade and colonize the whole plant, independently on symptom development. Latently infected propagating material is a major factor in their spreading. Therefore the use of bacteria-free planting stock has a basic importance in viticulture. Today several innovative diagnostic methods, mostly based on polymerase chain reaction, are available to detect and identify bacterial pathogens of grapevines. For production of bacteria-free plants, the use hot water treatment followed by establishment of in vitro shoot tip cultures is proposed.